Konsep Produksi dan Perilaku Produsen : Tafsir Ekonomi Islam Atas Konsep Produksi dan Perilaku Produsen Muslim - Rizky Amaliyah; Ilham, Muhammad; Wulandari, Devy; Sapa, Nasrullah Bin (Lembaga Pengkajian Pengembangan Pendidikan dan Kewirausahaan, 2026)
This research aims to examine the concept of production and producer behavior from the perspective of Qur'anic interpretation. In the context of Islamic economics, production is not only seen as a purely economic activity, but also as a form of worship that must be in line with sharia values. This study uses a qualitative approach based on library research by analyzing Qur'anic verses related to the work, creation, distribution, and social responsibility of producers, as well as tracing the interpretations of classical and contemporary mufassir. The results of the study show that the concept of production in the Qur'an contains the principles of blessing, justice, efficiency, and environmental sustainability. Meanwhile, the ideal producer behavior in the Qur'an reflects an attitude of trustworthiness, honesty, responsibility, not harming consumers, and not hoarding wealth excessively. Thus, production from the perspective of the interpretation of the Qur'an is not only aimed at meeting worldly needs, but also directed at achieving the benefits of the ummah and the pleasure of Allah SWT.